The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/s00415-002-0778-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of outpatient rehabilitation on quality of life in multiple sclerosis

Abstract: It is well accepted that rehabilitative treatment can be effective in reducing disability and optimizing quality of life (QoL) of people with multiple sclerosis (MS). The aim of this study was to evaluate the effects of a comprehensive outpatient rehabilitative treatment on QoL in patients suffering from MS. We selected 111 patients from a sample of 407 patients who had consecutively entered the MS Center of Catania (which is located in southern Italy) in 1998. Fifty-eight were randomly assigned to the study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 25 publications
(30 reference statements)
5
69
1
5
Order By: Relevance
“…Inpatient setting was associated with a significant improvement in functional impairment [], disability [23], functional independence [25,38] and HRQoL [25,26]. Trials conducted in outpatient setting demonstrated effectiveness of rehabilitation in improvement of muscular strength [22], walking capacity [30], functional independence [27,38], HRQoL [22,24,26]. Home-based rehabilitation produced significant improvement in HRQoL [34, 82,83] Below, we report the conclusions of several systematic reviews which searched to assess the effectiveness of multidisciplinary rehabilitation in PwMS to explore rehabilitation approaches in different settings.…”
Section: Cognitive Rehabilitationmentioning
confidence: 99%
“…Inpatient setting was associated with a significant improvement in functional impairment [], disability [23], functional independence [25,38] and HRQoL [25,26]. Trials conducted in outpatient setting demonstrated effectiveness of rehabilitation in improvement of muscular strength [22], walking capacity [30], functional independence [27,38], HRQoL [22,24,26]. Home-based rehabilitation produced significant improvement in HRQoL [34, 82,83] Below, we report the conclusions of several systematic reviews which searched to assess the effectiveness of multidisciplinary rehabilitation in PwMS to explore rehabilitation approaches in different settings.…”
Section: Cognitive Rehabilitationmentioning
confidence: 99%
“…Dlatego głównym celem rehabilitacji osób z SR jest utrzymanie optymalnej sprawności fizycznej, psychicz- [5]. Analiza wyników badań potwierdza efektywność rehabilitacji jako czynnika zmniejszającego niepełnospraw-ność tej grupy chorych, a także poprawiającego jakość ich życia, niezależnie od tego czy rehabilitacja prowadzona jest w środowisku szpitalnym czy domowym [6,7]. Proces rehabilitacji obejmuje diagnozowanie, leczenie wczesne, zapobieganie powikłaniom, ciągłość oraz integrowanie społeczne [8].…”
Section: Wstępunclassified
“…Wpły-wa również na obniżenie jakości życia chorych. Choroba w szczególności wpływa na stan psychiczny pacjentów, zwłaszcza na ich procesy emocjonalne [1,6,37]. Szeroko rozumiana poprawa jakości życia, funkcjonowania społecznego i zawodowego są możliwe poprzez edukację społeczną osób z SR. Może być ona realizowana w Stowarzyszeniach Osób ze Stwardnieniem Rozsianym lub Klubach Osób ze Stwardnieniem Rozsianym.…”
unclassified
“…It was stated in a Cochrane review that consisted of 14 randomized controlled and controlled clinical trials that a multidisciplinary rehabilitation approach was at the "strong evidence" level for short-term gains in the level of activity and participation in MS patients (1). There are a limited number of investigations about MS rehabilitation in the literature (1,(4)(5)(6)(7)(8)(9). Therefore, in our study, we aimed to review the sociodemographic and clinical features of the MS patients who were hospitalized at our inpatient clinic and the rehabilitation methods applied and to shed light on the studies that would be conducted on this subject.…”
Section: Introductionmentioning
confidence: 99%